Answer:
The answer to your question is
Explanation:
Data
Point (2, 3)
line y - 4 = -2(x + 3)
Process
1.- Solve for y the line given
y - 4 = -2(x + 3)
y - 4 = -2x - 6
y = -2x - 6 + 4
y = -2x - 2
2.- Get the slope of the new line
slope = 1/2
3.- Get the equation of the new line
y - y1 = m(x - x1)
y - 3 = 1/2(x - 2)
y - 3 = 1/2x - 1
y = 1/2x - 1 + 3
y = 1/2x + 2
4.- Get the coordinates of the new line
When x = 0
y = 1/2(0) + 2
y = 2 P (0, 2)
When y = 0
0 = 1/2x + 2
1/2x = -2
x = -4 Q (-4, 0)
5.- Get the coordinates of the previous line
y = -2x - 2
When x = 0
y = -2(0) -2
y = -2 R (0, -2)
When y = 0
0 = -2x - 2
-2x = 2
x = 2/-2
x = -1 S (-1, 0)